2021
DOI: 10.3389/fmicb.2021.744094
|View full text |Cite
|
Sign up to set email alerts
|

Differential Root Exudation and Architecture for Improved Growth of Wheat Mediated by Phosphate Solubilizing Bacteria

Abstract: Phosphorous (P) deficiency is a major challenge faced by global agriculture. Phosphate-solubilizing bacteria (PSB) provide a sustainable approach to supply available phosphates to plants with improved crop productivity through synergistic interaction with plant roots. The present study demonstrates an insight into this synergistic P-solubilizing mechanism of PSB isolated from rhizosphere soils of major wheat-growing agro-ecological zones of Pakistan. Seven isolates were the efficient P solubilizers based on in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
29
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 34 publications
(31 citation statements)
references
References 96 publications
2
29
0
Order By: Relevance
“…It is involved in oxidation and cyclization of 3 a -(2-amino-2-carboxy-ethyl)-4 and 5-dioxo hexahydoquinoline dicarboxylic acid in the final step of PQQ biosynthesis (Meyer et al, 2011 ). In our previous studies, we revealed gcd (accession numbers MK883706 ), pho (accession numbers MK883704 ; Rasul et al, 2021 ), and pqqE genes (accession numbers MT897167 ; Yahya et al, 2021 ) containing Ochrobactrum sp. SSR is multifaceted PSB.…”
Section: Discussionmentioning
confidence: 89%
See 4 more Smart Citations
“…It is involved in oxidation and cyclization of 3 a -(2-amino-2-carboxy-ethyl)-4 and 5-dioxo hexahydoquinoline dicarboxylic acid in the final step of PQQ biosynthesis (Meyer et al, 2011 ). In our previous studies, we revealed gcd (accession numbers MK883706 ), pho (accession numbers MK883704 ; Rasul et al, 2021 ), and pqqE genes (accession numbers MT897167 ; Yahya et al, 2021 ) containing Ochrobactrum sp. SSR is multifaceted PSB.…”
Section: Discussionmentioning
confidence: 89%
“…The applied bacterial strains solubilized RP and phytate. Previously these bacteria were reported to solubilize P from tricalcium phosphate (Yahya et al, 2021 ). Our data supports the view that the utilization of multiple P sources by bacteria assures that they release P in different substrates and environments, and exhibit a strong potential for applications (Wan et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations